Pricing and reimbursement experiences and insights in the European Union and the United States: Lessons learned to approach adaptive payer pathways. Issue 6 (22nd October 2016) - Faulkner, SD; Lee, M; Qin, D; Morrell, L; Xoxi, E; Sammarco, A; Cammarata, S; Russo, P; Pani, L; Barker, R
Abstract : Earlier patient access to beneficial therapeutics that addresses unmet need is one of the main requirements of innovation in global healthcare systems already burdened by unsustainable budgets. "Adaptive pathways" encompass earlier cross‐stakeholder engagement, regulatory tools, and iterative evidence generation through the life cycle of the medicinal product. A key enabler of earlier patient access is through more flexible and adaptive payer approaches to pricing and reimbursement that reflect the emerging evidence generated.